Telomere attrition and inflammatory load in severe psychiatric disorders and in response to psychotropic medications - Squassina, Alessio; Manchia, Mirko; Pisanu, Claudia; Ardau, Raffaella; Arzedi, Carlo; Bocchetta, Alberto; Caria, Paola; Cocco, Cristina; Congiu, Donatella; Cossu, Eleonora; Dettori, Tinuccia; Frau, Daniela Virginia; et al. (Neuropsychopharmacology (New York, N.Y.), 2020)
Individuals with severe psychiatric disorders have a reduced life expectancy compared to the general population. At the biological level, patients with these disorders present features that suggest the involvement of accelerated aging, such as increased circulating inflammatory markers and shorter telomere length (TL). To date, the role of the interplay between inflammation and telomere dynamics in the pathophysiology of severe psychiatric disorders has been scarcely investigated. In this study we measured T-lymphocytes TL with quantitative fluorescent in situ hybridization (Q-FISH) and plasma levels of inflammatory markers in a cohort comprised of 40 patients with bipolar disorder (BD), 41 with schizophrenia (SZ), 37 with major depressive disorder (MDD), and 36 non-psychiatric controls (NPC). TL was shorter in SZ and in MDD compared to NPC, while it was longer in BD (model F = 20.128, p = 8.73 × 10 , effect of diagnosis, F = 31.870; p = 1.08 × 10 ). There was no effect of the different classes of psychotropic medications, while duration of treatment with mood stabilizers was associated with longer TL (Partial correlation controlled for age and BMI: correlation coefficient = 0.451; p = 0.001). Levels of high-sensitivity C-Reactive Protein (hsCRP) were higher in SZ compared to NPC (adjusted p = 0.027), and inversely correlated with TL in the whole sample (r = -0.180; p = 0.042). Compared to NPC, patients with treatment resistant (TR) SZ had shorter TL (p = 0.001), while patients with TR MDD had higher levels of tumor necrosis factor-α (TNFα) compared to NPC (p = 0.028) and to non-TR (p = 0.039). Comorbidity with cardio-metabolic disorders did not influence the observed differences in TL, hsCRP, and TNFα among the diagnostic groups. Our study suggests that patients with severe psychiatric disorders present reduced TL and increased inflammation.